Eksplorasi Etnomatematika pada Aktivitas Menenun Desa Lailanjang dan Pengembangan Desain Pembelajaran Berbasis Budaya - Aleksius Madu; Petronela Loda Atandima (Media Pendidikan Matematika, 2026)
One of the cultures that exists in Lailanjang Village is weaving, which incorporates mathematical concepts. Weaving and culture can serve as a bridge between culture and mathematics, known as ethnomathematics. This study aims to describe the ethnomathematics of weaving activities in Lailanjang Village, discover the mathematical concepts involved, and design mathematics learning tools in accordance with these mathematical concepts. This study was conducted in East Sumba Regency with four subjects. The research method used was exploratory qualitative with an ethnographic approach. The researcher was the main instrument for collecting data through interviews, observations, documentation, and field notes. Data effectiveness was ensured through triangulation of sources. The results of the study show that there are values contained in the weaving process, namely the values of solidarity and attachment, descent and cultural identity, ethnicity and cultural identity, ethics, high moral response, critical values, aesthetic values, and value of price. In addition, there is ethnomathematics in the weaving process, namely the activities of counting, measuring, localizing, designing, and explaining. The mathematical concepts included in these activities are addition, counting, social arithmetic, geometry, and geometric transformations. The theoretical contribution of this research is the strengthening of the conceptual foundation of ethnomathematics, the reconstruction of mathematics concepts based on local culture, the development of an ethnomathematics integration framework in learning trajectories, contributions to contextual mathematics education theory, and the strengthening of local identity in scientific perspectives.Therefore, all of these mathematical concepts can be addressed by designing learning tools